The SMR reverse shoulder arthroplasty in rotator cuff arthropathy management - Beltrame, Alessandro; Di Benedetto, Paolo; Salviato, Daniele; Niccoli, Giuseppe; Gisonni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Cuff tear arthropathy (CTA) is a well-defined  degenerative pathology  of the shoulder. When conservative treatments are unable to permit a good quality of life, the reverse shoulder arthroplasty (RSA) can guarantee a good restitution of range of motion, function and strength of the shoulder without pain. In this paper we show our clinical, functional and radiological outcomes, as well as complications of RSA in patients with CTA. Methods: We analyzed 31 patients who underwent to reverse shoulder replacement with Modular Shoulder System (SMR, Systema Multiplana Randelli; Lima-LTO, San Daniele del Friuli, Italy) reverse shoulder system, between August 2010-July 2014. Results: A significant improvement in ROM and functional scores (Constant Shoulder Score and UCLA score) were observed in our cases series. At the time of follow-up  pain relief was detected in 28 patients and 3 patients declared mild pain. Overall, 90.3% of patients rated their satisfaction as good or excellent. Although  complications occur in a high percentage of patients in literature, no postoperative complications was observed in our cases series. Conclusions: Our results showed how reverse shoulder arthroplasty is a real solution to improve quality of life, to restore pain-free ROM, function and strength of the shoulder in patients where cuff tear arthropathy occurs.